Teknologi Blockchain sebagai Upaya Akuntabilitas Wakaf - Alya Zhafirah Nasywa; Setiawan Bin Lahuri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to explore how blockchain technology offers an innovative solution to improve accountability in waqf management. With its decentralization, transparency, and security properties, blockchain can overcome the challenges often faced in traditional waqf systems, such as lack of transparency, misuse of funds, and difficulties in asset tracking. In this study, we analyze the application of blockchain technology to waqf management, including how smart contracts can be used to automate and validate waqf transactions. In addition, this study explores the potential social and economic impact of blockchain implementation in strengthening public trust in waqf institutions. The research method involves conducting a systematic review of all existing literature, with a qualitative descriptive approach. The result of the study is that the adoption of this technology not only improves accountability and transparency, but can also encourage wider participation from the community in waqf activities. Thus, blockchain can be an important tool in the modernization of waqf management in the digital era as well as the potential in strengthening public trust, on technological adaptation.